Hubungan Pendapatan dan Asi Eksklusif dengan Kejadian Stunting pada Balita - Ni Wayan Erviana Puspita Dewi; Ni Komang Sri Ariani (Malahayati Nursing Journal, 2022)
ABSTRACT Stunting is the nutritional status of toddlers based on the height index for age. The maximum stunting standard according to World Health Organization (WHO) is 20% or one-fifth of the total number of children under five. The problem of stunting needs attention from all parties because of the high number of stunting cases. WHO in 2018 reported that the prevalence of stunting in Asia was higher than Africa. Various aspects can affect the high incidence of stunting, including education, social culture, pregnancy history, exclusive breastfeeding, health services, economy, political environment and others. The purpose of this study was to analyze the correlation between income and exclusive breastfeeding with the incidence of stunting in toddlers in the UPTD Work Area of Gianyar Health Center. Methods This research uses a correlation analytic design with a cross sectional approach. The sample in this study were mothers who had toddlers who met the inclusion criteria as many as 120 respondents. The data collection tool is a questionnaire related to factors related to stunting in toddlers. Bivariate analysis with Chi-Squere. Based on the results of the statistical analysis test with the chi square test, it shows that there is a significant relationship between income and the incidence of stunting in toddlers with a p-value of 0.007 (p value 0.05). The same thing is true with exclusive breastfeeding which states that there is a significant relationship between exclusive breastfeeding and the incidence of stunting, p-value = 0.036 (p value 0.05). Family income and exclusive breastfeeding are related to the incidence of stunting in toddlers Keywords: Stunting, Income, Exclusive Breastfeeding  ABSTRAK Stunting merupakan status gizi balita yang berdasarkan pada indeks tinggi badan menurut umur. Standar stunting maksimal menurut World Health Organization (WHO) yaitu 20% atau seperlima dari jumlah total anak balita.  Masalah stunting perlu mendapatkan perhatian dari semua pihak karena tingginya kasus stunting. WHO tahun 2018 melaporkan bahwa prevalensi stunting di Asia lebih tinggi di bandingkan dengan Afrika Berbagai aspek dapat mempengaruhi tingginya kejadian stunting antara lain pendidikan, sosial budaya, riwayat kehamilan, ASI Eksklusif, pelayanan kesehatan, ekonomi, lingkungan  politik dan lainnya. Tujuan penelitian ini untuk menganalisis hubungan antara pendapatan dan pemberian ASI Eksklusif dengan kejadian stunting pada balita di Wilayah Kerja UPTD Puskesmas Gianyar. Metode Penelitian ini menggunakan design analitik korelasi dengan pendekatan cross sectional. Sampel dalam penelitian adalah ibu yang mempunyai balita yang memenuhi kriteria inklusi sebanyak 120 responden. Alat pengumpulan data adalah kuesioner terkait factor-faktor yang berhubungan dengan stunting pada balita. Analisis bivariat dengan uji korelasi Chi-Squere. Berdasarkan hasil uji analisis statistic dengan uji chi square menunjukkan bahwa terdapat hubungan yang signifikan antara pendapatan dengan kejadian stunting pada balita dengan p-value 0.007 (p value0.05). Hal yang serupa juga dengan pemberian ASI Eksklusif yang menyatkan bahwa terdapat hubungan yang signifikan antara pemberian ASI Eksklusif dengan kejadian stunting p-value= 0.036 (p value 0,05). Pendapatan keluarga dan pemberian ASI Eksklusif berhubungan dengan kejadian stunting pada balita Kata Kunci: Stunting, Pendapatan, ASI Eksklusif